INHERITANCE IN THE COMMUNITY OF JUWONO VILLAGE, KERTOSONO SUBDISTRICT, NGANJUK REGENCY, EAST JAVA - Helmi, Hanum Rahmaniar; Poespasari, Ellyne Dwi; Soelistyowati, Soelistyowati; Erlangga, Afga Samudera; Agustine, Rahmawati Emma Audrya (jfpublisher, 2023)
In Juwono Village, Kertosono Subdistrict, Nganjuk Regency, East Java, inheritance follows a parental kinship system where descent is traced from both parents. All children, regardless of gender, have equal rights to their parents' inheritance, including original and joint property. Disputes may arise if any heir is dissatisfied with their share. This research aims to identify the system and the settlement of inheritance distribution in the Juwono Village Community, Kertosono Subdistrict, Nganjuk Regency, East Java. This research is a socio-legal research that can be classified into descriptive analytical research as this research examines the behavior of Juwono Village community members in the tradition of resolving disputes over the distribution of inheritance property to their heirs.The findings of this research revealed that in Juwono Village, inheritance is distributed based on parental kinship, granting equal rights to male and female heirs. Each heir receives an individual share to own and control. However, disputes often arise due to perceived inequities in the distribution, particularly concerning the shares of widows, widowers, biological children, adopted children, and stepchildren. These disputes, driven by differing interests and dissatisfaction, frequently lead to legal conflicts within the community.